Application of Wordwall Interactive Media to Increase Student Activity in Social Studies Learning at SBSM 5 Gombak, Malaysia - Hikmah Wifaqi (SOSEARCH : Social Science Educational Research, 2025)
This research aims to analyze the effectiveness of the use of interactive media Wordwall in increasing student activeness in the subject of Social Knowledge (IPS) at Sungai Mulia Guidance Studio 5 Gombak, Malaysia. Using Classroom Action Research (PTK) method in two cycles, each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 19 6th grade students. In the first cycle, the Wordwall "Spin the Wheel" feature was applied, while the second cycle used "Open the Box" in group discussions. The results showed an increase in student activeness from the initial condition of 21% to 52.6% in the first cycle, and increased again to 84.2% in the second cycle. The application of Wordwall is able to create a more lively, fun, and classroom atmosphere that encourages active student participation. The conclusion of this study is that Wordwall media not only increases student activeness, but also strengthens understanding of concepts and builds student confidence in the process of social studies learning. Thus, Wordwall is an interactive learning media that is effective and relevant to be applied in non-formal education